Current and Novel Therapeutics for Articular Cartilage Repair and Regeneration - Cong B; Sun T; Zhao Y; Chen M (Dove Medical Press, 2023)
Bo Cong,1,2 Tao Sun,1,2 Yuchi Zhao,1,2 Mingqi Chen1 1Department of Orthopedics, Yantaishan Hospital Affiliated to Binzhou Medical University, Yantai, 264003, People's Republic of China; 2Yantai Key Laboratory for Repair and Reconstruction of Bone & Joint, Yantai, 264003, People's Republic of ChinaCorrespondence: Mingqi Chen, Department of Orthopedics, Yantaishan Hospital, Yantai, 264003, People's Republic of China, Email c185463260@163.comAbstract: Articular cartilage repair is a sophisticated process that has is being recently investigated. There are several different approaches that are currently reported to promote cartilage repair, like cell-based therapies, biologics, and physical therapy. Cell-based therapies involve the using stem cells or chondrocytes, which make up cartilage, to promote the growth of new cartilage. Biologics, like growth factors, are also being applied to enhance cartilage repair. Physical therapy, like exercise and weight-bearing activities, can also be used to promote cartilage repair by inducing new cartilage growth and improving joint function. Additionally, surgical options like osteochondral autograft, autologous chondrocyte implantation, microfracture, and others are also reported for cartilage regeneration. In the current literature review, we aim to provide an up-to-date discussion about these approaches and discuss the current research status.Keywords: chondrogenesis, osteoarthritis, tissue engineering, mesenchymal stem cells, surgical repair